The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.12.05.519179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microdissection and culturing of adult lateral entorhinal cortex layer II neurons from APP/PS1 Alzheimer model mice

Abstract: Background: Primary neuronal cultures enable cell-biological studies of Alzheimer's disease (AD), albeit typically non-neuron-specific. The first cortical neurons affected in AD reside in layer II of the lateralmost part of the entorhinal cortex, and they undergo early accumulation of intracellular amyloid-β, form subsequent tau pathology, and start degenerating pre-symptomatically. These vulnerable entorhinal neurons uniquely express the glycoprotein reelin and provide selective inputs to the hippocampal memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…To further demonstrate the wider applicability of our model system for reverse engineering anatomically relevant networks for preclinical disease modelling, we used this system to culture neurons extracted from brain regions of interest from adult AD model animals. This method for the dissection and culturing of layer specific entorhinal and hippocampal neurons from AD model rats and mice builds upon our recently published protocol for extraction and culturing of LEC LII neurons from adult AD model APP/PS1 mice (39). We found that adult neurons from both AD model rats-(Figure 5) and mice (Figure S2) were able to re-form structural connections in vitro.…”
Section: Adult Entorhinal and Hippocampal Ad Neurons Reform Structura...mentioning
confidence: 80%
See 4 more Smart Citations
“…To further demonstrate the wider applicability of our model system for reverse engineering anatomically relevant networks for preclinical disease modelling, we used this system to culture neurons extracted from brain regions of interest from adult AD model animals. This method for the dissection and culturing of layer specific entorhinal and hippocampal neurons from AD model rats and mice builds upon our recently published protocol for extraction and culturing of LEC LII neurons from adult AD model APP/PS1 mice (39). We found that adult neurons from both AD model rats-(Figure 5) and mice (Figure S2) were able to re-form structural connections in vitro.…”
Section: Adult Entorhinal and Hippocampal Ad Neurons Reform Structura...mentioning
confidence: 80%
“…Our neural cultures comprised either commercially available rat embryonic cortical and hippocampal neurons (hereafter referred to as cortical-hippocampal networks), or lateral entorhinal cortex layer II neurons (LEC-LII), Dentate Gyrus granular neurons (DG-gl), CA3 pyramidal neurons (CA3-pyr) and CA1 pyramidal neurons (CA1pyr), freshly dissected from adult McGill-R-Thy1-APP ADmodel rats or APP/PS1 AD-model mice (hereafter referred to as adult entorhinal-hippocampal AD networks). The method for the dissection and culturing of adult hippocampal neurons was refined from our previously reported protocol for adult lateral-most LEC LII (lLEC-LII) neurons from APP/PS1 model mice (39). For all cultures, coating and establishment of an astrocytic feeder layer was conducted using the same protocol.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations